2015
DOI: 10.1002/cncr.29515
|View full text |Cite
|
Sign up to set email alerts
|

Are we missing an opportunity for cancer prevention? Human papillomavirus vaccination for survivors of pediatric and young adult cancers

Abstract: Survivors of pediatric and young adult cancers remain at risk for subsequent diseases, including those related to human papillomavirus (HPV) infection. Prevention of HPV acquisition through vaccination has become possible over the last decade. HPV vaccines have been shown to be safe and effective, yet rates of vaccination among childhood cancer survivors have remained low. Multiple factors, including stronger advocacy for this intervention from providers, could potentially increase vaccination and lead to lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…A study conducted among patients and maternal caregivers attending a survivor clinic at St. Jude Children's Research Hospital found that 32.6% (75 of 230) of cancer survivors initiated and 17.9% completed the 3‐dose vaccine series, whereas 34.3% (24 of 70) of healthy controls initiated and 20.0% completed the HPV vaccine series . Although these studies suggest that HPV vaccination rates among survivor populations are similar to those in the general population, the prevalence of HPV vaccination in this vulnerable population should be higher …”
Section: Vaccines For Cancer Preventionmentioning
confidence: 99%
See 3 more Smart Citations
“…A study conducted among patients and maternal caregivers attending a survivor clinic at St. Jude Children's Research Hospital found that 32.6% (75 of 230) of cancer survivors initiated and 17.9% completed the 3‐dose vaccine series, whereas 34.3% (24 of 70) of healthy controls initiated and 20.0% completed the HPV vaccine series . Although these studies suggest that HPV vaccination rates among survivor populations are similar to those in the general population, the prevalence of HPV vaccination in this vulnerable population should be higher …”
Section: Vaccines For Cancer Preventionmentioning
confidence: 99%
“…HPV immunization rates are substantially lower than rates of other childhood and adolescent immunizations. In addition to cost and parental concerns about vaccine safety, barriers to HPV vaccine uptake among adolescents and young adults include the misperceptions among some parents that HPV immunization is not needed for children who are not sexually active and that the receipt of the vaccine might increase promiscuity . Strategies to increase HPV vaccination include reminder/recall systems; practice‐focused interventions targeting staff, clinicians, and parents; assessment and feedback activities; and school‐based HPV vaccination programs …”
Section: Vaccines For Cancer Preventionmentioning
confidence: 99%
See 2 more Smart Citations
“…The over 400,000 survivors of childhood cancer in the U.S. represent a growing population with unique human papillomavirus (HPV)-related health risks. 1,2 Survivors of childhood cancer face a substantial risk of developing second cancers, 3,4 including HPV-related cancers. Nationally, the relative excess of HPV-associated malignancies was 40% among female survivors of childhood cancer and 150% among male survivors compared to the general population.…”
Section: Introductionmentioning
confidence: 99%